2001
DOI: 10.1093/jac/47.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, double-dummy study comparing the efficacy and safety of amoxycillin 1 g bd with amoxycillin 500 mg tds in the treatment of acute exacerbations of chronic bronchitis

Abstract: This randomized, multicentre, double-blind, double-dummy study compared the efficacy and safety of amoxycillin 1 g bd with amoxycillin 500 mg tds in 395 patients with a clinical diagnosis of acute exacerbation of chronic bronchitis (AECB). Patients were treated for 10 days and were assessed during therapy (days 3-5), after the end of therapy (days 12-15) and at follow up (days 28-35). In the intention-to-treat (ITT) population, clinical success rates at the end of therapy were 86.6% (162/187 patients) and 85.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Georgopoulos and colleagues36 compared the efficacy and safety of amoxycillin at different doses and observed a clinical success rate of 85.6% using 500 mg three times daily. Mertens and colleagues37 found no differences in clinical success between amoxycillin and azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Georgopoulos and colleagues36 compared the efficacy and safety of amoxycillin at different doses and observed a clinical success rate of 85.6% using 500 mg three times daily. Mertens and colleagues37 found no differences in clinical success between amoxycillin and azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Например, клиническая эффективность амоксицил лина -препарата выбора при оХОБЛ у пациентов группы низкого риска составляет 92 % [32], что вполне объяснимо крайне высокой антипневмокок ковой [33] и антигемофильной [34] активностью препарата на фоне минимального уровня резистент ности S. pneumoniae и H. influenzae в России. В анали зе T.File et al [35], в который были включены 6 про спективных исследований, клинический эффект амоксициллина достигнут у 43 / 44 (97,7 %) пациен тов с внебольничной пневмонией, ассоциированной даже с устойчивым S. pneumoniae (минимальная по давляющая концентрация амоксициллина -8 мг / л), включая 7 / 7 случаев инфекции, сопровождавшейся бактериемией.…”
Section: резюмеunclassified
“…Most studies of the aetiology of community-acquired pneumonia (CAP) have found S. pneumoniae to be the major pathogen, followed by H. influenzae; however, the proportions of S. pneumoniae and other pathogens vary considerably between studies, as shown in Table 1 [11][12][13][14][15][16][17][18][19][20][21]. Our ability to identify the infectious cause in all cases of CAP remains compromised as in 20-70% of hospitalised patients, no infectious agent is found from blood or sputum [22].…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%